Comparison of Social Studies Learning Outcomes Using Documentary Video Media for Grade VIII Students at SMP Negeri 1 Banawa - Hikma, Hikma; Nuraedah, Nuraedah; Misnah, Misnah; Iskandar, Iskandar (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to answer the following question: